USING STAD TO TEACH LISTENING NARRATIVE TEXT IN EFL CLASSROOM AT SMKN GUDO JOMBANG - Tajuk Deden Putra Wibowo Tajuk; Muh Fajar Fajar; Heny Sulistyowati Heny (JEELL (Journal of English Education, Linguistics and Literature), 2024)
The purpose of this study was to find out whether there were differences between classes taught by the STAD method and conventional methods. The research design used a quasi-experimental static group comparison, where there was no pre-test but only a post-test which was carried out at the end of the study. This research conducted at SMK Negeri Gudo. The population in this study amounted to 300 students divided into 10 classes and the number of samples taken was 2 classes. The experimental class is class X TKJ1 and the control class is class X TKJ 2. The total sample is 63 students with 31 students in the experimental group and 32 students in the control group. Both classes were taught for 4 meetings with the STAD method in the experimental class and the conventional method in the control class. The results showed that there were differences post-test result in the experimental class and the control class. Where the experimental group obtained an average value of 73.03 and the control group of 61.16.In testing the research hypothesis, the Mann-WhitneyU nonparametric test was used. The Mann-WhitneyU test results show the Asymp. Sig. (2-tailed) of .008 (<α = 0.05). It states that Ha is accepted and H0 is rejected, indicating that "There is a significant difference in academic achievement for listening skills between the students taught using STAD and the students taught using non-STAD teaching method”.